Nested scalar convolutions in multi-criteria problems - Voronin, A.; Savchenko, A. (Проблеми керування та інформатики, 2024)
A problem of structuring of the criteria set is considered in case of large dimension multi-criteria problems solving. A notion of the nested scalar convolution is introduced. The optimization problem is to determine the arguments by extremizing the objective function Essentially, this function is a scalar convolution of the criteria vector reflecting the utility function of the decision maker when solving a specific optimization problem. Розглянуто структурування множини критеріїв при розв’язуванні багатокритеріальних задач великої розмірності. Вводиться поняття вкладеної скалярної згортки. Задача оптимізації полягає у визначенні аргументів шляхом екстремізації цільової функції По суті, ця функція є скалярною згорткою вектора критеріїв що відображає функцію корисності особи, що приймає рішення при розвʼязанні конкретної задачі оптимізації.